Real and Virtual in the Educational Space of Modern Globalized Society - Gazniuk, L.M.; Petrusenko, N.Y.; Gorbenko, O.V.; Saltan, N.M. (KnE Social Sciences, 2021)
Globalization combines elements of integration and differentiation — common traits, extrapolated to single social groups, undergo a broad system of localization, adapting to the conditions of the new system of existence. In today’s globalized society, the real and the virtual are becoming so intertwined that it is increasingly difficult to define their boundaries. Two specific interpretations of the concept of «alternative globalism» are described: the first one is related to the use of this term to refer to social movement; the second one reflects some, including theoretical, critique of globalization, its manifestations and possible consequences. Structural-functional method, prognostic method, elements of schematization and generalization are used to clarify some issues of the philosophical paradigm of the modern educational space in the global and regional perspective. The study has revealed that the antiсipation of the future educational space is based on the analytics of actual changes in the status of knowledge. The focus of the research is the processes of mercantilization of knowledge, which indicates the commodity status of knowledge in modern society. The transition of society from consumption of mainly tangible goods to consumption of services, and subsequently to maximum consumption of information, was established. The concept of deterritorialization has shown that the essential characteristic of globalization is the loss of physical space in many social processes. A virtual theory related to the formation of «imaginary worlds» due to the imposition of different cultural and symbolic spaces: ethnic, technological, financial, ideological and media space is investigated. The study has revealed emergence of a «knowledge economy» society as a resource base of modern capitalism and the dialectical relations of «global and local» both in the structure of education and in the social system of the nation-state. Keywords: real, virtual, globalized society, deterritorialization, information-symbolic exchange, cultural and symbolic flows, functionalism of information, educational space